Public Preferences and Willingness to Pay for Bay Ecological Restoration - LI Jingmei; HAO Yanan; SHAN Jingzhu; ZHANG Xiaofan (Haiyang Kaifa yu guanli)
The implementation of ecological restoration based on public preferences is a key aspect of constructing beautiful bays and an important component of China's marine ecological civilization. This paper, based on the choice experiment method, takes the ecological restoration of Jiaozhou Bay as the research object and uses the RPL model to evaluate the public's preferences for the elements of bay ecological restoration, quantifying the public's preferences and willingness to pay for bay ecological restoration. The research results show that: ① Among the attributes of bay ecological restoration, the nearshore water quality, coastal landscape, coastal space, and marine biological resources significantly positively affect the residents' utility level, thereby enhancing the public's utility level. ② The annual willingness to pay of Qingdao residents for improving water quality, restoring biological populations, increasing coastal space, and enhancing coastal landscapes in bay ecological restoration is 89.83 CNY, 62.33 CNY, 28.33 CNY, and 19.33CNY, respectively. Based on this, the total willingness to pay of Qingdao residents for Jiaozhou Bay ecological restoration is estimated to be 1.449 billion CNY per year. The research conclusions can provide data support for formulating policies for bay ecological restoration and governance and shaping people-oriented high-quality bay ecological restoration.